Narciclasine enhances cisplatin-induced apoptotic cell death by inducing unfolded protein response-mediated regulation of NOXA and MCL1 - Ji Hae Lee; Seung Hee Seo; Jaegal Shim; Yong-Nyun Kim; Kyungsil Yoon (Cellular & Molecular Biology Letters)
Abstract Background Platinum-based chemotherapy is commonly used to treat non-small cell lung cancer (NSCLC); however, innate and acquired resistance is clinically seen in many patients. Hence, a combinatorial approach with novel therapeutic agents to overcome chemoresistance is a promising option for improving patient outcomes. We investigated the combinational anticancer efficacy of cisplatin and narciclasine in three-dimensional NSCLC tumor spheroids. Methods To assess the efficacy of cisplatin and narciclasine, cell viability assays, live/dead cell staining, cell death enzyme-linked immunosorbent assay (ELISA), western blot analysis for proteins related to apoptosis, and in vivo xenograft experiments were performed. The synergistic effects of cisplatin and narciclasine were elucidated through transcriptomic analysis and subsequent validation of candidate molecules by regulating their expression. To clarify the underlying molecular mechanisms, the activation of unfolded protein responses and kinetics of a candidate protein were assessed. Results Narciclasine inhibited viability of NSCLC tumor spheroids and augmented the sensitivity of cisplatin-resistant tumor spheroids to cisplatin by inducing apoptosis. After conducting bioinformatic analysis using RNA sequencing data and functional validation experiments, we identified NOXA as a key gene responsible for the enhanced apoptosis observed with the combination of cisplatin and narciclasine. This treatment dramatically increased NOXA while downregulating anti-apoptotic MCL1 levels. Silencing NOXA reversed the enhanced apoptosis and restored MCL1 levels, while MCL1 overexpression protected tumor spheroids from combination treatment-induced apoptosis. Interestingly, narciclasine alone and in combination with cisplatin induced unfolded protein response and inhibited general protein synthesis. Furthermore, the combination treatment increased NOXA expression through the IRE1α–JNK/p38 axis and the activation of p53. Cisplatin alone and in combination with narciclasine destabilized MCL1 via NOXA-mediated proteasomal degradation. Conclusions We identified a natural product, narciclasine, that synergizes with cisplatin. The combination of cisplatin and narciclasine induced NOXA expression, downregulated MCL1, and ultimately induced apoptosis in NSCLC tumor spheroids. Our findings suggest that narciclasine is a potential natural product for combination with cisplatin for treatment of NSCLC.